The Effect of Counseling with Decision Making Tools (ABPK) on the Fertilization Inhibition Process in the Postpartum Period in 2024 - Ita Herawati; Nyai Sulastri; Rusnah; Yeti Urianty; Eva Nova Lestarida Silaen (Postgraduate, University of Mataram, 2024)
This study examines the effect of counseling using Decision Making Tools (ABPK) on the use of fertilization inhibition methods during the postpartum period at TPMB Eva Lestarida Bekasi in 2024. ABPK serves as a standard guide in family planning counseling, focusing on client rights and informed choice. The research employs a quasi-experimental design with a one-group pre-test and post-test approach, involving 200 respondents. Data were analyzed using the Wilcoxon statistical test. Prior to counseling, 72% of respondents did not use fertilization inhibition methods. After ABPK counseling, the use of these methods increased to 71.5%, showing a significant change (p = 0.000). The findings indicate that ABPK-based counseling greatly influences patients' decisions, enabling them to choose the most appropriate fertilization inhibition method. These results highlight the effectiveness of ABPK in improving family planning counseling services by ensuring that patients make informed choices based on accurate information. ABPK is thus proven to be a valuable tool in educating patients and supporting their decisions regarding postpartum contraceptive methods.